2019
DOI: 10.1007/s10995-019-02797-2
|View full text |Cite
|
Sign up to set email alerts
|

Google AdWords and Facebook Ads for Recruitment of Pregnant Women into a Prospective Cohort Study With Long-Term Follow-Up

Abstract: Objectives Several types of epidemiologic studies suffer from decreasing participation rates, resulting in potential selection bias and delay or termination of studies. We aimed to determine the feasibility of online methods for recruitment of pregnant women into a prospective cohort study. Methods In addition to traditional recruitment through prenatal care providers, we advertized participation in the PRegnancy and Infant DEvelopment (PRIDE) Study, an ongoing prospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
(49 reference statements)
4
17
0
Order By: Relevance
“…While they conclude that online recruitment was more successful than o ine, only 3.6% of their actual participants were recruited via Facebook advertisements. Finally, Van Gelder et al, [62] reported greater success with traditional methods than paid Facebook promotions regarding recruitment of pregnant women into their prospective, long-term longitudinal study. They also report, similar to the current study, lower participation rates among women recruited through Facebook vs traditional methods.…”
Section: Discussionmentioning
confidence: 99%
“…While they conclude that online recruitment was more successful than o ine, only 3.6% of their actual participants were recruited via Facebook advertisements. Finally, Van Gelder et al, [62] reported greater success with traditional methods than paid Facebook promotions regarding recruitment of pregnant women into their prospective, long-term longitudinal study. They also report, similar to the current study, lower participation rates among women recruited through Facebook vs traditional methods.…”
Section: Discussionmentioning
confidence: 99%
“…We partnered with “Moeders voor Moeders” (Mothers for Mothers), an organisation that collects urine from women between gestational weeks 6 and 16 to extract human chorionic gonadotropin for the production of medication used in fertility treatment. Furthermore, we implemented intermittent Facebook and Google AdWords advertisements, participated in exhibitions at pregnancy fairs, and placed advertisements in magazines targeted at pregnant women.…”
Section: Methodsmentioning
confidence: 99%
“…The non‐traditional methods of recruitment not only added more inclusions, but also more diversity to the PRIDE Study population, especially in terms of maternal level of education. In terms of absolute numbers, however, the contribution of the online recruitment methods was limited and needs further refinement and extension, for example through optimal budget settings and addition of other social media . Furthermore, we are grateful for the collaboration with “Moeders voor Moeders,” but are unaware of similar initiatives in other countries.…”
Section: Commentmentioning
confidence: 99%
“…19 , 20 Google Ads Keywords Planner, initially designed for e-commerce campaigns, has been used recently as a tool for the recruitment of Google users to clinical trials. 21 , 22 This tool may also serve as an epidemiological data source and enables both qualitative and quantitative analysis of a large number of keywords associated with the given phrases in the chosen language, location and timeframe. 23 These properties were used in a study on a series of dermatological studies, 23 27 as well as in paper on heartburn-related searches across six Western countries.…”
Section: Introductionmentioning
confidence: 99%